LOCOMOTOR DISABILITY AMONG ADULT POPULATION OF A NORTH INDIAN DISTRICT: A CROSS SECTIONAL STUDY - Shankul Jain; Najam Khalique; Sameena Ahmad; Mohd Najmul Aqib Khan; Mohd Maroof; Mohammad Salman Shah (Universitas Airlangga, 2023)
Introduction: Disability, which has been deemed as a significant public health problem in our country, in any form, be it correctable or not, tends to hamper the day to day life of the affected person. It affects their personal as well as professional life to a great extent, and creates a lack of confidence and difficulty in social interactions. To assess the burden of locomotor disability, its socio-demographic correlates, and suggest measures to improve the life of people with disability. Methods: It was a cross-sectional study, conducted in areas under the rural and urban health training centers, using a pretested and validated questionnaire along with appropriate examination of the involved system. A total of 900 individuals were included. The study duration was July 2017 to June 2018. The collected data were analyzed using SPSS 20.0. Results: The total prevalence of disability (of any type) contributed to 13.6% while locomotor disability was found to be 4.44% in the study population. Significant association of locomotor disability was observed with age, gender, marital status and occupation (p <0.05). Conclusion: Availability and accessibility of rehabilitation centers at the peripheral areas, along with creating community awareness towards it, may prove to be a step in the right direction to alleviate the discomfort of the people living with disability.